Izucenie fiziologiceskoj stoimosti fiziceskoj nagruzki pri podgotovke kvalificirovannych borcov - Reksha, Yu. M.; Bulatetsky, S. V.; Rastegaeva, I. V.; Pokhachevskiy, D. A.; Lazarova, A. V. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
Frequency analysis of the heart rate variability (HRV) was used to objectively quantify the adaptive reserves of the body of the qualified fighters before and after sports training. The structure of the variability of the adaptive reserves is studied, and options for their interpretation are proposed depending on the spectral characteristics of the HRV. The characteristic features and fundamental differences of the autonomic regulation of the heart rate of the athletes before and after sports training were revealed and analyzed. The conclusion is made about the high sensitivity of the method, the possibility of applying this approach to study the individual "price" of adaptation to physical activity and sports training, depending on the type, intensity of physical activity, qualifications and training of the athlete.